Evaluación de la viabilidad técnica para el uso de materiales lignocelulósicos (bagazo de caña en mezcla con cáscara de yuca) como biopolímero biodegradable en la fabricación de envases desechables - Febres Asprino, Victor Eloy (2024)
The environmental management of the use of single-use plastic is today one of the most important challenges, due to the environmental impact that its use entails. Its disposable nature and low recycling rate significantly affect its harmful potential, generating various adverse effects, such as accumulation of waste, contamination of water sources and soil, impact on terrestrial and marine flora and fauna, and negative impact on the environment. human health. Hence the need to develop viable alternatives that allow mitigating the negative impact of plastic, such as the one proposed in this research work. The general objective was to evaluate the viability of the use of lignocellulosic material (cane bagasse mixed with cassava peel) as degradable biopolymers, through technical agglomeration tests, with the purpose of determining its potential as a raw material in the creation of disposable packaging. Using a mixed approach, explanatory research was developed that sought to specify the effects of using sugarcane bagasse and cassava bark as raw materials for the creation of disposable plates. For this, a comparative analysis of the characteristics of the product obtained with sugarcane bagasse mixed with cassava peel at different concentrations (30% and 40%) was carried out. The results obtained in the research were positive regarding treatments that presented high performance in the hardness test with an average of 83,607 Ha, but with a low permeability time of 5,013 min on average, which facilitates the material decomposition process\; However, optimal results were not obtained when subjecting the biopolymer to mechanical compression and traction tests.